The Importance and Role of Imam Al-Sarakhsi‟s Mabsut in Islamic Fiqh - Qosimov , Mirjalol (International Journal of Psychosocial Rehabilitation, 2020)
This paper is about the scientific and practical significance of “Mabsut” by Shams al-A'imma Muhammad b. Ahmad b. Abi Sahl Abu Bakr al-Sarakhsi, a representative of the 11th-century Mawarounnahr Hanafi sect, and the article also seeks to clarify the significance of “Mabsut” written by Sarakhsi. In particular, the financial issues presented in “Mabsut” are as relevant today as they were in the past and have not lost their social relevance in modern life. Sarakhsi's work differs from the works of his contemporaries in this area, and it is distinguished by the subtlety of issues.